Safety and placement stability for the Children's Home Network kinship navigator program. (August 2020) - Littlewood, Kerry; Cooper, Lawrence; Pandey, Abhishek
Abstract: Background: With the passage of the Families First Prevention Act, kinship navigator programs have growing support as an intervention to connect kinship families to needed resources. Growing evidence has helped to showcase the outcomes, but no study has shared follow up outcomes past twelve months. Objective: This study examined the 12, 24 and 36 month follow up child safety (substantiated abuse record) and placement stability (disruption in placement) outcomes from state administered secondary data for children whose caregivers participated in the Children's Home Network-Kinship Navigator Program (CHN-KN). Setting: Study participants were 240 (60 in each group) randomly selected kinship caregivers who were enrolled in four treatment groups in CHN-KN (Standard Kinship Navigator, Kinship Navigator with Innovations, Kinship Navigator with Peer-to-Peer only, and Usual Child Welfare). Methods: Repeated measures anovas were used to show between group differences for each study group. Results: Results show that children living with caregivers who received Kinship Navigator Programs (Kinship Navigator Peer to Peer and Kinship Navigator with Innovations) were the least likely to be involved in a substantiation of child abuse or neglect and most likely to remain in the home of a relative at 12, 24 and 36 month follow up. Conclusions: Results suggest that the kinship navigator programs could improve child safety and placement stability. This study can help to inform the replication of the CHN-KN model and provide additional supported evidence to inform practice.